The Relationship Between Knowledge And Exposure To Digital Media And Risky Sexual Behavior Among Adolescents At SMPN Satap 2 Batujaya, Karawang - Suryanto, Yanto; Pebriani, Emi; RS, Danur Azissah; Sholihin, Rizki; Permana, Didi (Student Scientific Journal, 2026)
Risky sexual behavior among adolescents is a health issue influenced by reproductive health knowledge and exposure to digital media. Low knowledge and high exposure to digital media with sexual content can increase the risk of risky sexual behavior in adolescents. This study aims to determine the relationship between knowledge and exposure to digital media and risky sexual behavior among adolescents at SMPN Satap 2 Batujaya Karawang. This study used a quantitative design with a cross-sectional approach. The study population was 168 students, with a sample of 89 respondents selected using proportional purposive sampling. Data were collected using a questionnaire and analyzed using the chi-square test. The results showed a relationship between knowledge and risky sexual behavior in adolescents (p-value = 0.003 (